Student as Online Prostitution Crime Offender (Study in Semarang City) - Madjid, Dinda Zuliani; Meilindari, Anastasia; Handayani, Lilik; Agustinus, Eko; Maulana, Agi Febri (Law Research Review Quarterly, 2019)
The purpose of this study is to find out how students can become commercial sex workers and what is behind these deviations. This research is a qualitative research with a descriptive approach. The subjects of this study consisted of three students who are currently commercial sex workers in online prostitution. This research shows that one of the factors driving students to become commercial sex workers in online prostitution is formed because of economic, social and environmental factors. In addition to being a commercial sex worker, students can usually also be hired as a date. Customers usually after getting an agreement can meet in person at an agreed place beforehand. All of these transaction processes can be done quickly and privately. There is agreement between the two before engaging in the practice of prostitution.